2013
DOI: 10.2967/jnumed.113.120659
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cardiac Sympathetic Nerve Density with N-11C-Guanyl-meta-Octopamine and Tracer Kinetic Analysis

Abstract: Most cardiac sympathetic nerve radiotracers are substrates of the norepinephrine transporter (NET). Existing tracers such as 123 Imetaiodobenzylguanidine ( 123 I-MIBG) and 11 C-(-)-meta-hydroxyephedrine ( 11 C-HED) are flow-limited tracers because of their rapid NET transport rates. This prevents successful application of kinetic analysis techniques and causes semiquantitative measures of tracer retention to be insensitive to mild-to-moderate nerve losses. N-11 C-guanyl-(-)-meta-octopamine ( 11 C-GMO) has a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
(21 reference statements)
1
24
1
Order By: Relevance
“…This was better heart-to-blood contrast than the ratio measured for [ 18 F] 1 , which was H/B = 3.0 ± 0.5. 17, 18 Final heart-to-liver (H/L) ratios for [ 18 F] 2 were 2.2 ± 0.8. Due to faster clearance of activity from the liver, contrast between heart and liver was a little better for [ 18 F] 1 , with final H/L = 2.5 ± 0.3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was better heart-to-blood contrast than the ratio measured for [ 18 F] 1 , which was H/B = 3.0 ± 0.5. 17, 18 Final heart-to-liver (H/L) ratios for [ 18 F] 2 were 2.2 ± 0.8. Due to faster clearance of activity from the liver, contrast between heart and liver was a little better for [ 18 F] 1 , with final H/L = 2.5 ± 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…The slower neuronal uptake rate makes the rate constant associated with this process more identifiable from the cardiac PET kinetics, and the rapid uptake and long retention in storage vesicles eliminates one rate constant from the kinetic model, leading to more reliable and consistent parameter estimates. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PET imaging with [ 11 C]HED cannot accurately quantify regional nerve densities due to the rapid neuronal uptake rates. Raffel et al [ 116 ] recently synthesized N- 11 C-guanyl-(-)-meta-octopamine ([ 11 C]GMO), which has a much slower NET transport rate and is trapped in storage vesicles. Initial results have shown that [ 11 C]GMO provides robust and sensitive quantitative measurements of regional cardiac sympathetic nerve density and might be able to detect mild-to-moderate sympathetic nerve loss at the early stages of cardiac denervation.…”
Section: Other Biomarker-based Probesmentioning
confidence: 99%
“…Therefore, an important limitation to this study is the use of the semiquantitative RI. Along these lines, it has been debated that the 11 C-HED RI may not be sensitive enough to detect mild-to-moderate nerve loss (29). Recently, a fully quantitative kinetic model has been established for 11 C-HED (30) and confirmed that the quantitative parameter, volume of distribution, is nonlinearly related to SUV and RI, especially in the setting of lower radiotracer uptake.…”
mentioning
confidence: 99%